Relationship between cognitive dysfunction and the promoter methylation of PER1 and CRY1 in patients with cerebral small vessel disease - Xu, Yiwen; Wang, Yugang; Jiang, Yi; Liu, Mengqian; Zhong, Wen; Ge, Zhonglin; Sun, Zhichao; Shen, Xiaozhu (Frontiers in Aging Neuroscience, 2023)
Background and purpose The prevalence of cerebral small vessel disease (CSVD) is increasing due to the accelerating global aging process, resulting in a substantial burden on all countries, as cognitive dysfunction associated with CSVD is also on the rise. Clock genes have a significant impact on cognitive decline and dementia. Furthermore, the pattern of DNA methylation in clock genes is strongly associated with cognitive impairment. Thus, the aim of this study was to explore the connection between DNA promoter methylation of PER1 and CRY1 and cognitive dysfunction in patients with CSVD. Methods We recruited patients with CSVD admitted to the Geriatrics Department of the Lianyungang Second People’s Hospital between March 2021 and June 2022. Based on their Mini-Mental State Examination score, patients were categorized into two groups: 65 cases with cognitive dysfunction and 36 cases with normal cognitive function. Clinical data, 24-h ambulatory blood pressure monitoring parameters, and CSVD total load scores were collected. Moreover, we employed methylation-specific PCR to analyze the peripheral blood promoter methylation levels of clock genes PER1 and CRY1 in all CSVD patients who were enrolled. Finally, we used binary logistic regression models to assess the association between the promoter methylation of clock genes (PER1 and CRY1) and cognitive dysfunction in patients with CSVD. Results (1) A total of 101 individuals with CSVD were included in this study. There were no statistical differences between the two groups in baseline clinical data except MMSE and AD8 scores. (2) After B/H correction, the promoter methylation rate of PER1 was higher in the cognitive dysfunction group than that in the normal group, and the difference was statistically significant (adjusted p < 0.001). (3) There was no significant correlation between the promoter methylation rates of PER1 and CRY1 in peripheral blood and circadian rhythm of blood pressure (p > 0.05). (4) Binary logistic regression models showed that the influence of promoter methylation of PER1 and CRY1 on cognitive dysfunction were statistically significant in Model 1 (p < 0.001; p = 0.025), and it still existed after adjusting for confounding factors in Model 2. Patients with the promoter methylation of PER1 gene (OR = 16.565, 95%CI, 4.057–67.628; p < 0.001) and the promoter methylation of CRY1 gene (OR = 6.017, 95%CI, 1.290–28.069; p = 0.022) were at greater risk of cognitive dysfunction compared with those with unmethylated promoters of corresponding genes in Model 2. Conclusion The promoter methylation rate of PER1 gene was higher in the cognitive dysfunction group among CSVD patients. And the hypermethylation of the promoters of clock genes PER1 and CRY1 may be involved in affecting cognitive dysfunction in patients with CSVD.